Twenty K. R. Narayanan Orations : Essays by Eminent Persons on the Rapidly Transforming Indian Economy. - Jha, Raghbendra (Canberra : ANU Press, 2021)
This collection of the Narayanan Orations is thus at once both an expert account of key aspects of the economic development process in India and a peek into India's potential in the future.
Australia and India: Combining Technology and Entrepreneurship to Innovate the Future -- Oration 18: 2016 K.R. Narayanan Oration -- The New Economics of Financial Inclusion in India -- Oration 19: 2017 K.R. Narayanan Oration -- India: A Resurgent Maritime Nation, Harnessing the Blue Economy -- Oration 20: 2018 K.R. Narayanan Oration -- Dismantling Inequality through ASSURED Innovation.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Economic history; Economic policy; India--Economic conditions--1947-.; Electronic books